2018
DOI: 10.1021/acscatal.8b04524
|View full text |Cite
|
Sign up to set email alerts
|

Amine Transaminase fromExophiala Xenobiotica—Crystal Structure and Engineering of a Fold IV Transaminase that Naturally Converts Biaryl Ketones

Abstract: Amine transaminases are frequently used for the production of chiral amines starting from prochiral ketones. These amines can be applied as active pharmaceutical ingredients or drug precursors. However, there are still limitations to the use of amine transaminases when it comes to bulky ketone substrates, such as biaryl ketones. Using data mining, an (R)-selective amine transaminase from Exophiala xenobiotica was identified which naturally converts biaryl ketone substrates to the corresponding amines with up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 44 publications
(57 reference statements)
0
43
0
Order By: Relevance
“…SEC unexpectedly revealed that 90% of Ts RTA in solution exists as a tetramer, with only 10% adopting the dimeric form ( Figure S5 ). Other highly similar RTAs, including At RTA (4ce5, 81% identity) (Łyskowski et al, 2014 ), and RTAs from Nectria haematococca (4cmd, 78% identity) (Sayer et al, 2014 ), Exophiala xenobiotica (6fte, 70% identity) (Telzerow et al, 2019 ), and Aspergillus fumigatus (4uug, 73% identity) (Thomsen et al, 2014 ) are reported as dimers based on their crystal packing. Two thermostable BCATs, belonging to the same fold type IV as RTAs, with hexameric structures have recently been reported by Isupov et al ( 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…SEC unexpectedly revealed that 90% of Ts RTA in solution exists as a tetramer, with only 10% adopting the dimeric form ( Figure S5 ). Other highly similar RTAs, including At RTA (4ce5, 81% identity) (Łyskowski et al, 2014 ), and RTAs from Nectria haematococca (4cmd, 78% identity) (Sayer et al, 2014 ), Exophiala xenobiotica (6fte, 70% identity) (Telzerow et al, 2019 ), and Aspergillus fumigatus (4uug, 73% identity) (Thomsen et al, 2014 ) are reported as dimers based on their crystal packing. Two thermostable BCATs, belonging to the same fold type IV as RTAs, with hexameric structures have recently been reported by Isupov et al ( 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the rationally engineered (S)-selective ATA from V. fluvialis catalyzed an ortho-biaryl ketone to the corresponding (S)-biaryl amine. 47 Bornscheuer and coworkers, 16 in parallel to us, 48…”
Section: Figure 1 Examples Of Biaryl-containing Drugs: Valsartane (1mentioning
confidence: 89%
“…In 2016, a rationally engineered ( S )‐selective ATA from V. fluvialis catalyzed an ortho‐biaryl ketone to the corresponding biaryl amine . Similarly, two biocatalysts recently found by data mining, namely the ( R )‐selective ATA from Exophiala xenobiotica (EX‐ωTA) and Asperguillus fumigatus (4CHI‐TA), catalyzed efficiently the amination of meta ‐ and para ‐biaryl ketones. Further structure‐guided protein engineering resulted in broader substrate scope and improved stability which paved the way for the straightforward approach A in Scheme .…”
Section: Chemoenzymatic Synthetic Cascadesmentioning
confidence: 99%